Apolipoprotein D facilitates rabies virus propagation by interacting with G protein and upregulating cholesterol - Zhang, Hongyan; Liang, Xingxue; Li, Duoduo; Zhang, Chuanliang; Wang, Wenfeng; Tang, Rongze; Zhang, Hongyun; Kiflu, Abraha Bahlbi; Liu, Cheng; Liang, Jingjing; Li, Xiaoning; Luo, Ting Rong (Frontiers in Immunology, 2024)
Rabies virus (RABV), causes a fatal neurological disease, consists of unsegmented negative-strand RNA, which encodes five structural proteins (3′-N-P-M-G-L-5′). Apolipoprotein D (ApoD), a lipocalin, is up regulated in the nervous system after injury or pathological changes. Few studies have focused on the role of ApoD during virus infection so far. This study demonstrated that ApoD is upregulated in the mouse brain (in vivo) and C8-D1A cells (in vitro) after RABV infection. ApoD overexpression facilitated RABV replication in C8-D1A cells. Additionally, ApoD interacted with RABV glycoprotein (G protein) to promote RABV replication by upregulating the cholesterol level. These findings revealed a novel role of ApoD in promoting RABV replication and provided a potential therapeutic target for rabies.